2004
DOI: 10.1095/biolreprod.104.031088
|View full text |Cite
|
Sign up to set email alerts
|

Secreted and Placental Membrane Forms of Folate-Binding Protein Occur Sequentially During Pregnancy in Swine1

Abstract: The objective was to understand how two forms of folate-binding protein interact to accomplish folate transport during pregnancy in swine. Specific folate binding was measured in uterine flushings during the estrous cycle and early pregnancy and in allantoic fluid (secreted form) and placental membranes (membrane form) throughout later pregnancy. In addition, the localization of the secreted form of folate-binding protein (sFBP) in uterine wall sections was assessed. Uterine flushings were collected on Days 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…In more recent studies, it was reported that the two forms were produced sequentially during the 114-d gestation of the pig. The sFBP form increased dramatically in uterine flushings at the time of conceptus elongation (Day [11][12][13][14][15] and was present in the intrauterine glands until Day 20 of gestation [7,10]. We have demonstrated that genetic polymorphisms in the sFBP gene were associated with differences in uterine capacity, but not litter size, because of simultaneous effects on ovulation rate [11].…”
Section: Introductionmentioning
confidence: 81%
“…In more recent studies, it was reported that the two forms were produced sequentially during the 114-d gestation of the pig. The sFBP form increased dramatically in uterine flushings at the time of conceptus elongation (Day [11][12][13][14][15] and was present in the intrauterine glands until Day 20 of gestation [7,10]. We have demonstrated that genetic polymorphisms in the sFBP gene were associated with differences in uterine capacity, but not litter size, because of simultaneous effects on ovulation rate [11].…”
Section: Introductionmentioning
confidence: 81%
“…Among these genes, CN161469 was found to be similar to methylcrotonoyl-Coenzyme A carboxylase 2 (beta), which suggests that it possesses the similar biological functions. In addition, the gene U89949.1, which encodes a folate binding protein that is involved in the transport of foliate (Vallet et al, 2001; Kim and Vallet, 2004), played an major role in the network. This finding was in accordance with the results of the assessment of the GO categories and pathway analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies on folate transport mechanisms using placental cell lines or mammalian placenta. 24,25) FR, which transports folates by endocytosis, and RFC, which mediates bidirectional folate transport, are thought to be involved in the folate transport mechanisms in the placenta, but Keating et al have suggested that other carriers, which differ from both FR and RFC, are also involved in folate transport under an acidic condition in BeWo cells. 26) Hence it has been suggested that there are more than two transport mechanisms in folate transport in the placenta, and further investigation is necessary to clarify these complex mechanisms.…”
Section: Discussionmentioning
confidence: 99%